Asymmetric and bi-continuously structured polyethersulfone (PES) membranes with superior water flux for ultrafiltration application - Chang, Chao-Ching; Yu, Szu-Ting; Su, Jenn Fang; Cheng, Liao-Ping (Journal of polymer research, 2022)
This work reports a fabrication of asymmetric polyethersulfone (PES) membranes from the water/γ-butyllactone (GBL)/polyvinylpyrrolidone (PVP)/PES system using non-solvent induced phase separation (NIPS) process. Different amounts of PVP and PES are added into the environmentally friendly solvent, GBL, to form the dope solutions and their effects on the morphological, physical, permeation, and filtration properties of formed membranes are systematically studied. The results demonstrate that the pore size on the top surface and the size of macrovoids in the bulk increase with increasing PVP content and decreasing PES amount in the dope. In the optimal conditions (PVP/PES ratio approaches 1, in particular), the macrovoids disappears and the pores evolve into three-dimensional pore networks in PES matrix. This unique bi-continuous membrane exhibits a remarkable water permeation flux of nearly 1000 L•m −2 h −1 and a BSA rejection of 91%.